Correlation Between Vitamin D3 and Fasting Blood Sugar in Type 2 Diabetes Mellitus Patients and Normal Individuals in a Bangladeshi Population - Islam, Md. Tazul; Mozaffor, Miliva; Islam, Md. Ehsanul; Roy, Heera Lal (Journal of Advances in Internal Medicine, 2020)
Background and Aims: Controversies prevail on association of vitamin D level and type 2 diabetes mellitus. The present study aims to compare serum 25-hydroxycholecalciferol (vitamin D3) level and fasting blood glucose in type 2 diabetes mellitus patients and healthy subjects and evaluate their association in both groups.Methods: This cross-sectional, observational study was done in Department of Biochemistry, Sylhet MAG Osmani Medical College, Bangladesh, between July 2015 and June 2016. The patients were selected from medicine out-patients departments (MOPD) of Sylhet MAG Osmani Medical College Hospital and Sylhet Diabetic Hospital, Bangladesh. A total of 135 study subjects were selected following convenient consecutive sampling technique. They grouped into case (Group A) i.e. 65 patients having type 2 diabetes mellitus, and control (Group B), i.e. 70 patients apparently healthy subjects (non-diabetic). Initial evaluation of the patients done by history and clinical examination was recorded in the preformed data collection sheet. Fasting blood glucose was measured by enzymatic method, while serum 25-hydroxycholecalciferol (vitamin D3) was measured by radioimmunoassay (RIA).Results: The mean age of 42.02±3.29 years in case (Group A); while 41.35±3.97 years in control (Group B). There were 33 male (50.76%) and 32 (49.23%) female in group A, while 35 (50%) male and 35 (50%) female in group B. No significant age difference was observed between the groups (p=0.284). Serum 25-hydroxycholecalciferol in cases (Group A) was 55.73±9.02 ng/ml and in controls (Group B) 53.77±10.86 ng/ ml (p=0.255). Fasting blood glucose was 161.98±62.47 mg/dl in cases (Group A) and 86.92±15.74 mg/dl in controls (Group B) (p